Pore-scale modeling and simulation of flow, transport, and adsorptive or osmotic effects in membranes: the influence of membrane microstructure - Calo, Victor; Iliev, O.; Lakdawala, Z.; Leonard, K.; Printsypar, G. (Springer Link, 2015)
The selection of an appropriate membrane for a particular application is a complex and expensive process. Computational modeling can significantly aid membrane researchers and manufacturers in this process. The membrane morphology is highly influential on its efficiency within several applications, but is often overlooked in simulation. Two such applications which are very important in the provision of clean water are forward osmosis and filtration using functionalized micro/ultra/nano-filtration membranes. Herein, we investigate the effect of the membrane morphology in these two applications. First we present results of the separation process using resolved finger- and sponge-like support layers. Second, we represent the functionalization of a typical microfiltration membrane using absorptive pore walls, and illustrate the effect of different microstructures on the reactive process. Such numerical modeling will aid manufacturers in optimizing operating conditions and designing efficient membranes.